Effect of Acid Etching and Er:YAG Laser Enamel Conditioning on the Microleakage of Glass Carbomer Fissure Sealants - Ozveren, Neslihan; Uslu, Yesim Sesen; Donmez, Nazmiye (UI Scholars Hub, 2020)
Objective: This study aimed to evaluate the effects of Er:YAG laser used alone or in combination with acid etching as surface conditioners on the microleakage of a glass carbomer fissure sealant for permanent molar teeth. Methods: Forty sound human permanent molar teeth were randomly divided into four experimental groups based on enamel etching methods: group I, no surface conditioning; group II, 37% phosphoric acid etching; group III, Er:YAG laser etching; and group IV, sequential laser etching and acid etching. After surface conditioning procedures were conducted, the teeth were sealed with a glass carbomer seal. The teeth were subjected to thermocycling with 2500 cycles at 5±2 °C to 55±2 °C for 24 h. Subsequent microleakage was assessed via dye penetration under a stereomicroscope. Results: Group II showed the lowest microleakage scores. Groups III and IV exhibited similar score distribution, which was lower than that of group I. Conclusions: Laser etching and acid etching decrease the microleakage probability of glass carbomer sealants, and acid etching alone provides a more suitable surface for these sealants. Sequential laser etching and acid etching have no additional benefit in comparison with acid etching alone and yield worse results than those of the other tested methods.